2016
DOI: 10.1186/s12864-016-2492-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel comparative pattern analysis approach identifies chronic alcohol mediated dysregulation of transcriptomic dynamics during liver regeneration

Abstract: BackgroundLiver regeneration is inhibited by chronic ethanol consumption and this impaired repair response may contribute to the risk for alcoholic liver disease. We developed and applied a novel data analysis approach to assess the effect of chronic ethanol intake in the mechanisms responsible for liver regeneration. We performed a time series transcriptomic profiling study of the regeneration response after 2/3rd partial hepatectomy (PHx) in ethanol-fed and isocaloric control rats.ResultsWe developed a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 99 publications
3
18
0
Order By: Relevance
“…Our data also show that the ALD Liver-Chip picked up the impact of ethanol treatment on genes involved in the metabolism of alanine, aspartate, and glutamate. In line with previous data shown the link between FLD and DNA damage in hepatocytes 18 , our analysis revealed upregulation of POLE and POLD2 61 , both involved in DNA replication and repair, as well as of RAD51 and FANCB, which are expressed at DNA damage sites and implicated in homologous recombination 62,63 (Fig. 3e).…”
Section: Ethanol-induced Steatosis In the Liver-chipsupporting
confidence: 92%
“…Our data also show that the ALD Liver-Chip picked up the impact of ethanol treatment on genes involved in the metabolism of alanine, aspartate, and glutamate. In line with previous data shown the link between FLD and DNA damage in hepatocytes 18 , our analysis revealed upregulation of POLE and POLD2 61 , both involved in DNA replication and repair, as well as of RAD51 and FANCB, which are expressed at DNA damage sites and implicated in homologous recombination 62,63 (Fig. 3e).…”
Section: Ethanol-induced Steatosis In the Liver-chipsupporting
confidence: 92%
“…In order to unmask the potential effects of RA and DEAB treatments on transcriptomic changes during early development, we analyzed the clutch-averaged data using an unbiased dynamic pattern analysis approach to categorize the gene expression profiles along all possible discretized patterns (Kuttippurathu et al, 2016). Each pattern is based on the direction of up- or down-regulation above a 2-fold threshold (three possibilities: up-regulation, down-regulation, or no change) at each of the three recovery time points relative to the stage the treatment was terminated (early gastrula; t=0), yielding 3*3*3 = 27 possible discretized patterns.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the RA and DEAB groups for their effect on gene expression relative to the unperturbed temporal pattern observed in the control samples, we adapted a recently developed unbiased approach named COMPACT for analyzing time-series differential transcriptomic profiles across multiple experimental conditions (Kuttippurathu et al, 2016). In this scheme, we started with the statistically significant genes within each treatment group (two-way ANOVA; q<0.05), and constructed discrete patterns based on differential gene expression between RA and control groups (81 possible patterns, with up-, down- and no-regulation at t=0, 1.5, 3 and 4.5 h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic alcohol consumption causes oxidative mitochondria DNA (mtDNA) damage in hepatocytes and inhibits liver regeneration after partial hepatectomy . However, our previous publication showed that a reduced‐size (50%) liver from rats fed alcohol regenerated well when transplanted to a normal host.…”
mentioning
confidence: 99%